2012
DOI: 10.1016/j.exer.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

In vivo detection of experimental optic neuritis by pupillometry

Abstract: Optic neuritis is an inflammatory demyelination of optic nerve often occurring in multiple sclerosis (MS) patients. Mice with experimental autoimmune encephalomyelitis (EAE), an MS model, develop optic neuritis, but it is detected histologically after sacrifice, limiting the ability to monitor progression or treatment in vivo. We examined whether pupillary light responses measured by pupillometry can identify eyes with optic neuritis in EAE mice. C57BL/6 mice were exposed to unilateral light flashes of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…In this study, we show that SIRT1 overexpression actively attenuates the symptoms of disease progression in EAE. The SIRT1 activator resveratrol (SRT501) was shown to suppress EAE, exhibiting protection against myelin breakdown in the EAE animal model (26)(27)(28). Our present observations provide further evidence supporting the beneficial effects of SIRT1 on myelin-forming OLs in EAE spinal cord.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, we show that SIRT1 overexpression actively attenuates the symptoms of disease progression in EAE. The SIRT1 activator resveratrol (SRT501) was shown to suppress EAE, exhibiting protection against myelin breakdown in the EAE animal model (26)(27)(28). Our present observations provide further evidence supporting the beneficial effects of SIRT1 on myelin-forming OLs in EAE spinal cord.…”
Section: Discussionsupporting
confidence: 77%
“…SIRT1 has been linked to neurodegenerative diseases (23)(24)(25). A pharmaceutical formulation of resveratrol (SRT501) that activates SIRT1 prevents neuronal damage and long-term neurologic dysfunction in EAE (26)(27)(28). Importantly, either SRT501 or other SIRT1-activating compounds regulate inflammation in EAE (26)(27)(28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We immunized C57BL/6 mice with myelin oligodendrocyte glycoprotein peptide (MOG 35–55 ), a widely applied method to induce EAE in animals [1,5,12,13]. Both MS and EAE are characterized by inflammation and neurodegeneration in the spinal cord and the brain [12].…”
Section: Introductionmentioning
confidence: 99%
“…Meeker et al 12) reported that inter-examiner disagreement regarding the pupillary reaction was 39% for manual examinations compared with 1% for automated pupillometers. Hence, studies to define the relationship between clinical manifestations and PLR determined by automated pupillometer have been conducted in various fields 1 2 5 6 7 9 15 17 18) .…”
Section: Discussionmentioning
confidence: 99%